Dentin matrix protein 1 and HUVEC-ECM scaffold promote the differentiation of human dental pulp stem cells into endothelial lineage: implications in regenerative medicine - Ganapathy, Amudha; Narayanan, Karthikeyan; Chen, Yinghua; Villani, Cassandra; George, Anne (Frontiers in Physiology, 2024)
Reprograming of the dental pulp somatic cells to endothelial cells is an attractive strategy for generation of new blood vessels. For tissue regeneration, vascularization of engineered constructs is crucial to improve repair mechanisms. In this study, we show that dentin matrix protein 1 (DMP1) and HUVEC-ECM scaffold enhances the differentiation potential of dental pulp stem cells (DPSCs) to an endothelial phenotype. Our results show that the differentiated DPSCs expressed endothelial markers CD31 and VE-Cadherin (CD144) at 7 and 14 days. Expression of CD31 and VE-Cadherin (CD144) were also confirmed by immunofluorescence. Furthermore, flow cytometry analysis revealed a steady increase in CD31 and VE-Cadherin (CD144) positive cells with DMP1 treatment when compared with control. In addition, integrins specific for endothelial cells were highly expressed during the differentiation process. The endothelial cell signature of differentiated DPSCs were additionally characterized for key endothelial cell markers using gene expression by RT-PCR, Western blotting, immunostaining, and RNA-seq analysis. Furthermore, the angiogenic phenotype was confirmed by tubule and capillary sprout formation. Overall, stimulation of DPSCs by DMP1 and use of HUVEC-ECM scaffold promoted their differentiation into phenotypically, transcriptionally, and functionally differentiated bonafide endothelial cells. This study is novel, physiologically relevant and different from conventional strategies.